How relevance of philosophy, science and philosophy science through the study of mathematical logic? - Farida, Farida; Rotama, Andra; Dharmawan, Dharmawan; Pahrudin, Agus (Universitas Islam Raden Intan Lampung, INDONESIA, 2024)
Background: Philosophy, science, and the philosophy of science serve as interconnected systems of expression that can be utilized as benchmarks and standards of truth across various fields. Through the study of mathematical logic, the complexity of thought will contribute to analyzing a strong epistemological and methodological foundation for modern science, while also reinforcing the philosophical underpinnings of science in understanding nature and scientific processes.Aim: This research aims to provide information and descriptions about the relevance of philosophy, science and philosophy of science through the study of mathematical logic.Method: The writing of this work is included in qualitative research using the literature review method.Result: Mathematical logic is a very important element in life as the source of all actions that print the history of everyone's life wherever and whenever, so this also means that mathematical logic has important relevance in efforts to explain things in terms of philosophy and science. and philosophy of science.Conclusion: The relevance of philosophy, science, and the philosophy of science lies in their interconnected relationships, all driven by the common goal of seeking truth. A deeper understanding of this relationship can fortify the philosophical foundations in comprehending scientific truth and processes. Through the study of mathematical logic, this understanding offers valuable contributions to education and the advancement of knowledge.